2017
DOI: 10.1007/s10508-017-1083-5
|View full text |Cite
|
Sign up to set email alerts
|

Are Anal Sex Roles Associated with Preferences for Pre-Exposure Prophylaxis Administration Modalities Among Men Who Have Sex with Men?

Abstract: The current study sought to examine awareness of, willingness to use, and preferences for available and theoretical administration modalities for HIV pre-exposure prophylaxis (PrEP) and the association of anal sex roles with these concepts among a sample of men who have sex with men (MSM) in Paris, France. Broadcast advertisements were placed on a popular geosocial-networking smartphone application for MSM to direct users to complete a Web-based survey. MSM answered questions on their recent engagement in cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Access, retention, and adherence are important limiting factors of the efficacy of both PrEP and ART programs, and long-acting (LA) drug development holds the promise to solve some of these backdrops and became a game changer in the management of HIV [2]. For PrEP, willingness to use LA among MSM increased in recent years, after the dissemination of preliminary positive results [3]. Convenience (easiness of use, integration into the routine, administration setting, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Access, retention, and adherence are important limiting factors of the efficacy of both PrEP and ART programs, and long-acting (LA) drug development holds the promise to solve some of these backdrops and became a game changer in the management of HIV [2]. For PrEP, willingness to use LA among MSM increased in recent years, after the dissemination of preliminary positive results [3]. Convenience (easiness of use, integration into the routine, administration setting, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This study also identified significant associations between the number of male sex partners, the HIV serological status of male sex partners, recreational drug use, HSV-2 infection status, and the willingness to take LAI-PrEP among MSM with oral PrEP experience. Previous studies reported on factors associated with MSM’ willingness to take LAI-PrEP or the preference for LAI-PrEP, including demographic (e.g., age [ 22 , 31 , 35 ], ethnicity [ 23 , 33 , 35 , 39 ], educational level [ 21 , 27 , 34 ], income [ 22 ], and insurance [ 39 ]), behavioural (e.g., sex roles [ 20 , 31 ], number of male sexual partners [ 34 , 35 ], HIV serological status of male sex partners [ 21 ], condom use [ 19 ], and HIV testing [ 20 ]), HIV risk perception-related [ 21 , 27 ], and PrEP-related factors (e.g., PrEP use experience [ 22 , 27 , 33 , 35 ]). The factors, such as demographic characteristics and HIV-related behaviours, in this study were similar to those in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results compare individual and network variables between those who did and did not participate in this type of condomless sex during the past 6-month time period. We used two separate outcomes as recent literature has examined how HIV risk perception and one's ability to negotiate condom usage may differ depending on preferred sex roles in MSM [24]. Because each outcome was measured at both the initial assessment and subsequent follow-up visits, both variables were examined as repeated measures.…”
Section: Study Analysismentioning
confidence: 99%
“…Rates of new infections are especially high for black men who have sex with men (MSM), with 2015 surveillance estimates indicating that black MSM accounted for almost 39% of all new HIV infections among MSM [2][3][4][5]. In addition, HIV diagnoses among young black MSM (i.e., ages [13][14][15][16][17][18][19][20][21][22][23][24] increased 87% between 2005 and 2014 [5]. The HIV Prevention Trials Network (HPTN) 061 study, the largest prospective cohort study among black MSM from six U.S. cities, found a high overall HIV incidence (3.0%) (5.9 percent for young black MSM ≤30 years old) [6].…”
Section: Introductionmentioning
confidence: 99%